A Systematic review for sudden cardiac death in hypertrophic cardiomyopathy patients with Myocardial Fibrosis: A CMR LGE Study - Reddy, Sahadev T; Paladino, Antonio T; Silva, Nackle J; Doyle, Mark; Vido, Diane A; Biederman, Robert WW (Journal of Cardiology and Cardiovascular Medicine, 2019)
Background: Hypertrophic cardiomyopathy (HCM) patients have a predisposition for malignant VT/VF and consequently, sudden cardiac death (SCD). In single center studies, late gadolinium enhancement (LGE) defined fibrosis has been linked to VT/VF. However, despite innumerable investigations, SCD has not been definitely attributable to LGE. Explanations for these are believed to be related to insufficient statistical power. Methods: We performed an electronic search of MEDLINE, PubMed: and CMR abstracts for original data published or presented between Jan 2001 to Mar 2011. Key search terms: HCM, LV fibrosis, SCD and LGE. Studies were screened for eligibility based on inclusion criteria: referral for CMR exam with LGE for HCM; and follow-up for incidence of VT/VF and SCD. Categorical variables were evaluated between patient groups via Chi-square test. Results: A total of 64 studies were initially identified. Of these, 4 (6.3%) were identified and included (n = 1063 patients). Three prospective and one retrospective study were included. LGE was detected in 59.6% of patients. As expected, the presence of myocardial fibrosis was associated with VT/VF (x2 = 6.5, p < 0.05; OR 9.0, (95% CI 1.2 to 68.7). Moreover, myocardial fibrosis strongly predicted SCD (x2 = 6.6, p < 0.05; OR 3.3 (95% CI 1.2 to 9.7). Conclusion: Despite single center CMR studies, LGE has consistently predicted VT/VF while prediction of SCD has remained paradoxically unlinked. Although the lack of studies meeting our criteria limited our ability to perform a comprehensive meta-analysis, we have been able to demonstrate for the first time that LGE-defined fibrosis is a predictor of SCD in patients with HCM0.